Scaptotrigona marialiceae, a new species of neotropical stingless bee (Hym., Anthophila), from southern Brazil - Laroca, Sebastião; Almeida, Maria Christina de (Acta Biológica Paranaense, 2015)
Scaptotrigona marialiceae, a new species of neotropical stingless bee (Hym., Anthophila), from southern Brazil